Quantum Computing and Its Impact on Cryptography the Future of Secure Communication - Nandi, Sudheer; Vani YS, Kalai; Bhat, Archana; G. Poshamallu, G. Poshamallu; Shukla, Sushil (Journal of Neonatal Surgery, 2025)
Traditional public key cryptography becomes vulnerable because it depends on mathematical hardness assumptions such as factorization and discrete logarithms yet Shor’s algorithm and other quantum algorithms defeat these assumptions. Research performed on current literature in conjunction with quantum-resistant algorithm progress establishes the immediate requirement for moving toward systems protected from quantum attacks. An analysis along with simulation of algorithmic resilience helps understand future secure communication patterns